Conflict as a factor in the implementation of legal activities - Свиридюк, Н. П.; Мінченко, О. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The aim of the article is to research the conflict related to legal activities in the context of its practicalcomponent. It highlights the conflict and special responsibility as features of professional lawyers’ activitiesand defines alternative opportunities for extra-judicial resolution of disputes.